Analysis of Monitoring and Optimization of Electrical Energy Consumption at the Faculty of Dentistry, University of North Sumatra (USU) Using a Smart Metering System - Rakha Zahri Andresna; Solly Aryza; Beni Satria (Sean Institute, 2025)
The increasing consumption of electrical energy in academic environments, including the Faculty of Dentistry, University of North Sumatra (FKG USU), demands a more efficient energy monitoring and optimization system. This study aims to analyze the pattern of electrical energy consumption at FKG USU and optimize its use using a Smart Metering System. The methods used in this study include collecting energy consumption data through smart meters, analyzing consumption patterns using statistical and data mining approaches, and simulating optimization scenarios based on energy efficiency strategies. The results show that the use of a Smart Metering System can improve energy efficiency by reducing electricity consumption by up to (percentage if any) through more optimal electricity load management and user awareness of energy use. With this system, FKG USU can implement more effective energy saving strategies, reduce electricity operational costs, and contribute to environmental sustainability.